Analysis of the Quality of Village Office Employees in Buol Regency - Sri Yanti U.M. Armin (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The low quality of human resources, especially employees at the Kulango Village Head Office, Biau District, Buol Regency affects the quality of their work because in this case they do not really master the field of work they do. This study aimed to explore the quality of employees at the Kulango Village Head Office, Biau District, Buol Regency. This descriptive study employed a survey approach. Conducted from August to September 2019, this study involved 24 employees and officers at the Kulango Village Head Office, Biau District, Buol Regency. The data collected were primary data and secondary data. Primary data obtained through interviews, observation, and documentation. The data obtained were processed using frequency table data analysis techniques. The results showed that the quality of the apparatus resources at the Kulango Village Head Office, Biau District, Buol Regency was good in terms of indicators of knowledge, skills, abilities, and experience. However, the strategic plan and understanding of job descriptions for the apparatus of the Kulango Lurah Office, Biau District, Buol Regency must be improved. Although other indicators already have good results, improvements need to be made in order to produce quality apparatus resources.